Lipid profile in pre-eclampsia in comparison with normal subjects - Manish Kumar Misra; Devendra Nath Tiu; Rina Sharma (International Journal of Medical Research and Review, 2016)
Introduction: The present study was designed to evaluate the association of dyslipidemia (abnormal lipid metabolism) in pre-eclampsia in comparison with non pregnant women, normotensive pregnant women and post partum subjects.Material ad Methods: This study was conducted on 200 subjects who were further divided in four groups (50 subjects in each group). The four groups were non pregnant subjects, normotensive pregnant subjects, pre-eclamptic patients and post partum subjects. Each serum sample from different groups was evaluated for total cholesterol (mg/dl), HDL-cholesterol (mg/dl), LDL-cholesterol (mg/dl), VLDL-cholesterol (mg/dl) and triglyceride (mg/dl).Result: On comparison of non pregnant subjects, normotensive pregnant subjects and post partum subjects with pre-eclamptic patients, the levels of total cholesterol, LDL cholesterol, VLDL cholesterol and triglycerides were found to be significantly increased (p values ≤ 0.001) and that of HDL cholesterol levels were found to be statistically significantly (p values ≤ 0.001) in pre-eclamptic patients.Conclusion: Deranged lipid metabolism in pre-eclampsia is associated with development of atherosclerotic diseases which increases the morbidity and mortality in mother as well as foetus. The various factors responsible for development of dyslipidemia and its prevention need to be studied and evaluated.